2016
DOI: 10.1080/2162402x.2016.1189051
|View full text |Cite
|
Sign up to set email alerts
|

A novel TLR7 agonist reverses NK cell anergy and cures RMA-S lymphoma-bearing mice

Abstract: Toll-like receptor 7 (TLR7) agonists are potent immune stimulants able to overcome cancer-associated immune suppression. Due to dose-limiting systemic toxicities, only the topically applied TLR7 agonist (imiquimod) has been approved for therapy of skin tumors. There is a need for TLR7-activating compounds with equivalent efficacy but less toxicity. SC1, a novel small molecule agonist for TLR7, is a potent type-1 interferon inducer, comparable to the reference TLR7 agonist resiquimod, yet with lower induction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 51 publications
3
23
0
Order By: Relevance
“…The peritumoral administration of imiquimod preserved the immunogenicity of the tumor and prolonged tumor control by maintaining high numbers of activated T and NK cells during BRAFi therapy. These findings fit to the observations that imiquimod has manifold effects on the activation of NK and T cells . We cannot exclude that other cell types might also be affected, since imiquimod as an immune response modifier has pleiotropic effects on different immune and nonimmune cell types …”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The peritumoral administration of imiquimod preserved the immunogenicity of the tumor and prolonged tumor control by maintaining high numbers of activated T and NK cells during BRAFi therapy. These findings fit to the observations that imiquimod has manifold effects on the activation of NK and T cells . We cannot exclude that other cell types might also be affected, since imiquimod as an immune response modifier has pleiotropic effects on different immune and nonimmune cell types …”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, TLR7A has pleiotropic effects on T and NK cells and induces autophagic cell death in melanoma cells . Moreover, a recent study showed that a novel TLR7A reversed NK cell anergy and induced antitumor CD8 + T cell responses . Therefore, we assessed if treatment with a TLR7A as an immune modulator would be efficient in prolonging sensitivity to BRAFi.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent clinical study confirmed that MGN1703 treatment in HIV-1 infected patients on ART has a dual potential by increasing HIV-1 transcription and enhancing cytotoxic NK cell activation [179]. Other agonists able to boost NK cell effector functions against cancer cells are the ones binding TLR7 [180, 181]. These latter compounds have also been reported to increase both CD8+ T cell- and NK cell-mediated lysis of HIV-1-infected cells [172].…”
Section: Targeting Nk Cells In Hiv-1 Therapymentioning
confidence: 99%